2013
DOI: 10.1371/journal.pone.0083823
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Antibiotic Resistance Genes in the Gut Microflora of Individuals from Diverse Geographies and Age-Groups

Abstract: The spread of antibiotic resistance, originating from the rampant and unrestrictive use of antibiotics in humans and livestock over the past few decades has emerged as a global health problem. This problem has been further compounded by recent reports implicating the gut microbial communities to act as reservoirs of antibiotic resistance. We have profiled the presence of probable antibiotic resistance genes in the gut flora of 275 individuals from eight different nationalities. For this purpose, available meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 38 publications
(57 reference statements)
3
67
0
1
Order By: Relevance
“…With an estimated 1% to 3% of the developed world undergoing antibiotic treatment on a daily basis (3), the dynamic environment of the human intestine benefits (and may suffer in some cases) from metagenome accessibility of these genes on conjugative elements, viral particles, and plasmids (46,(52)(53)(54). Interestingly, in a study of genomic variation in over 200 individuals, conjugative elements with resistance functions were found to have the highest SNP density of all annotatable genes (55).…”
Section: The Mobility Of Antibiotic Resistance Genes Encoded In the Mmentioning
confidence: 99%
“…With an estimated 1% to 3% of the developed world undergoing antibiotic treatment on a daily basis (3), the dynamic environment of the human intestine benefits (and may suffer in some cases) from metagenome accessibility of these genes on conjugative elements, viral particles, and plasmids (46,(52)(53)(54). Interestingly, in a study of genomic variation in over 200 individuals, conjugative elements with resistance functions were found to have the highest SNP density of all annotatable genes (55).…”
Section: The Mobility Of Antibiotic Resistance Genes Encoded In the Mmentioning
confidence: 99%
“…The study also found multiple antibiotic resistance genes on contigs with integrase and transposase, indicating the possibility that these clusters are part of mobile genetic elements, such as conjugative transposons. Furthermore, 97% of the gut metagenomes harbored resistance genes to tetracycline, 95% to bacitracin, and 95% to tetracycline 59. Another metagenome analysis evaluated the gut microbiome from 162 individuals (encompassing 4.1 million genes) and found 1,093 antibiotic resistance genes 60.…”
Section: Role Of Horizontal Gene Transfer In the Spread Of Antibioticmentioning
confidence: 99%
“…Analysis of resistance against 68 classes and subclasses of antibiotics in 252 fecal metagenomes of individuals from three countries, Spain, Denmark and the U.S., show that global resistomes are significantly impacted by antibiotics approved for animal use as well as those that have been in use for the longest time [90]. The existence of these global “resistotypes” has also been shown in other studies, pointing to resistance to tetracycline as the most common genotype among individuals from different nationalities, and increased abundance and diversity of AMR in Spanish, Chinese, French or Italian cohorts compared to cohorts of Americans or Danish people [59, 90, 91]. …”
Section: Introductionmentioning
confidence: 92%
“…Tcr genes are also shared between mothers and infants; however, encoded by different organisms; Bacteroides , Ruminococcaceae and Clostridiaceae like taxa in mothers; and Streptococci in infants [57]. Nonetheless, other reports point to an infant gut resistome that is unique and different from that of the mothers, and that includes resistance to broad-spectrum β-lactam antibiotics, suggesting that early environmental determinants (different from maternal ones) also shape AMR development in the infant gut [58, 59]. In fact, lifestyle factors related to subsistence, diet and other cultural drivers strongly shape the GI microbiome [60, 61].…”
Section: Introductionmentioning
confidence: 99%